An Analysis of theClassroom Tests in Primary Schools of West Pokot County, Kenya - Kipsaina, Joseph Katam; Nabwire, Violet Kafwa (African Journal of Education and Practice, 2016)
Purpose: Focus in excelling in national examinations in primary school has influenced teaching and learning process in the classroom. The classroom process is however very essential in determining learning achievements. The purpose of the study was to analyze the nature of classroom tests in primary schools in West Pokot County. Thus, the objectives of the study were; to determine the influence of classroom tests on learner motivation, identify types of classroom tests and to assess the use of tests in instructional decision making. Methodology: The study was guided by Stufflebeam's Evaluation Model. A Conceptual framework was also used to show the interplay between the variables under study. The study employed a descriptive survey design and adopted mixed methods approach in data collection. The study combined both simple random and stratified proportionate sampling to select a total of 353 participants. A structured questionnaire consisting of 54 items was used to collect quantitative and some qualitative data. Cronbach's Alpha reliability test was computed to estimate internal consistency of the questionnaire, and an overall reliability index of 0.724 was realized. Further, classroom observation, interview and document analysis were also used to collect qualitative data. Results: The study revealed that the testing practice adopted by teachers in public primary schools was mainly teacher centred and to drill pupils to pass KCPE. The study also found that teachers' own testing practices can motivate pupils. Further, it was established that objective questions were the most preferred by teachers. Common instructional decisions made by teachers based on tests related to pupils' grading, diagnosis of learning difficulties, checking pupils' progress, preparing terminal progress reports and gauging learners' level of mastery of content. Unique contribution to practice and policy: The study concluded that classroom tests in public primary schools in West Pokot influences learning achievements of pupils.The study recommends that schools should adopt classroom assessment method in evaluating learning in public primary schools.